AMOC Recovery in a Multicentennial Scenario Using a Coupled Atmosphere‐Ocean‐Ice Sheet Model. Issue 16 (25th August 2020) - Ackermann, L.; Danek, C.; Gierz, P.; Lohmann, G.
Abstract: We simulate the two Coupled Model Intercomparison Project scenarios RCP4.5 and RCP8.5, to assess the effects of melt‐induced fresh water on the Atlantic meridional overturning circulation (AMOC). We use a newly developed climate model with high resolution at the coasts, resolving the complex ocean dynamics. Our results show an AMOC recovery in simulations run with and without an included ice sheet model. We find that the ice sheet adds a strong decadal variability on the freshwater release, resulting in intervals in which it reduces the surface runoff by high accumulation rates. This compensating effect is missing in climate models without dynamic ice sheets. Therefore, we argue to assess those freshwater hosing experiments critically, which aim to parameterize Greenland's freshwater release. We assume the increasing net evaporation over the Atlantic and the resulting increase in ocean salinity, to be the main driver of the AMOC recovery. Plain Language Summary: The Atlantic Ocean circulation is an important factor within the Earth's climate system. Part of this overturning are specific regions in the North Atlantic where water masses get heavier and sink down. It is speculated that huge amounts of fresh water could disturb this process and weaken the circulation. Because of global warming, one source of this fresh water might be melt water from the Greenland ice sheet. Global warming will also lead to stronger precipitation over Greenland. We show in different future scenarios that the Greenland ice sheet is not only melting but also growing in some areas. The amount of melt water that flows into the ocean shows a strong fluctuation. We find that the melting of the Greenland ice sheet will not have a big effect on ocean circulation. Key Points: The Atlantic meridional overturning circulation recovers after a slowdown in CMIP's RCP8.5 scenario The Greenland ice sheet acts as a freshwater source and sink, compensating melting by local ice growth and shows little effect on the AMOC The interbasin atmospheric freshwater flux is a main driver for the AMOC recovery